Diagnostic accuracy of lung ultrasound to predict weaning outcome: a systematic review and meta-analysis - Zhang, Zhiyang; Guo, Li; Wang, Huawei; Zhang, Ze; Shen, Limin; Zhao, Heling (Frontiers in Medicine, 2024)
Background This systematic review and meta-analysis aim to systematically assess the diagnostic accuracy of lung ultrasound in predicting weaning failure from mechanical ventilation in critically ill patients. Methods We searched the relevant literature up to January 2024 in the databases Web of Science, Cochrane Library, Embase, and PubMed. Two researchers independently screened eligible studies and extracted data; disagreements, if any, were resolved through discussion or consultation with a third-party expert. The quality of the included studies was assessed using the Quality Assessment of Diagnostic Accuracy Studies-2 tool. Statistical analyses were performed using Review Manager version 5.3 and Stata version 18.0, applying bivariate random-effects models to estimate sensitivity, specificity, diagnostic odds ratios, and their 95% confidence intervals, as well as to summarize receiver operating characteristic curves. Inter-study heterogeneity was assessed using the I-squared statistic, and potential sources of heterogeneity were explored by meta-regression analysis. The study follows the guidelines for Preferred Reporting Items for Systematic Reviews and Meta-Analyses in reporting. Results Fourteen studies were included in the systematic review, of which 13 studies (totaling 988 patients) were included in the meta-analysis. The meta-analysis revealed an overall sensitivity of 0.86 (95% confidence interval: 0.77–0.91) and a specificity of 0.75 (95% confidence interval: 0.66–0.83) for lung ultrasound in predicting extubation failure. The area under the receiver operating characteristic curve was 0.87 (95% confidence interval: 0.84–0.89). Meta-regression analysis identified lung ultrasound thresholds, reference standards (extubation outcomes), and study flow and time bias as significant factors influencing diagnostic accuracy. Conclusion This systematic review and meta-analysis demonstrated that lung ultrasound has high diagnostic accuracy in predicting extubation failure in mechanically ventilated critically ill patients. Despite some study heterogeneity, lung ultrasound proved to be a reliable predictive tool for extubation failure. Future research should focus on standardizing the definition of extubation failure, exploring the impact of different thresholds on the predictive ability of lung ultrasound, and validating its application in various clinical settings to enhance its utility and accuracy in clinical practice. Systematic review registration This systematic review and meta-analysis was registered with PROSPERO (registration number: CRD42024555909). The study adhered to the guidelines set by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Details of the PROSPERO protocol can be found in Supplementary Table 1.